Effect of hydro-alcoholic extract of Rhodiola imbricata on growth performance, immunomodulation, antioxidant level and blood biochemical parameters in broiler chickens at high altitude cold desert - KALIA, SAHIL; BHARTI, VIJAY KUMAR; GIRI, ARUP; VIVEK, PRINCE; KUMAR, BHUVNESH; UDAYABANU, MALAIRAMAN (The Indian Journal of Animal Sciences, 2017)
Extremes of climate and hypobaric hypoxia cause poor growth performance in broiler chickens at high altitude.The current study was designed to investigate the effect of hydro-alcoholic extract of Rhodiola imbricata onantioxidant, cytokines, blood biochemical and growth performance of broilers at high altitude (3500 m). For invivostudy, one day-old broiler chicks of average initial body weight 36.40±0.42 g were randomly assigned to seven groups in three replicates (10 chicks in each replicate) as per completely randomized design. Experimental groups included control (fed basal diet), and treatment T1, T2, T3, T4, T5, and T6 which received hydro-alcoholic extract of Rhodiola imbricata in drinking water @ 100, 150, 200, 300, 400, and 800 mg/kg body weight of chicken respectively, along with basal diet. Blood samples were collected at 0, 21st, and 42nd day. HPLC analysis of extract revealed the presence of salidroside and p-tyrosol. As a result of this study, birds in T5 group had significantly higher body weight as compared to other groups. Furthermore, they had significantly higher total antioxidant capacity, free radical scavenging activity, interleukin-2, total protein, globulin, HDL level and lower malondialdehyde, interleukin-6, cholesterol, triglyceride, LDL, glucose, A/G, ALT, AST level as compared to control group. Our results suggest that, Rhodiola imbricata extract @ 400 mg/kg body weight of chicken, exhibited beneficial effect on growth performance and therefore, can be used as a phytogenic feed additive for broiler chickens.